2010
DOI: 10.1016/j.memsci.2009.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Syndiotactic polypropylene copolymer membranes and their performance for oxygen separation

Abstract: Syndiotactic poly(propylene- -olefin) copolymers with controlled microstructure and desired properties for oxygen enrichment have been synthesized via metallocene catalysts. The controlled incorporation of comonomers as pendant branch mainly improved the oxygen permeability, but the oxygen/nitrogen selectivity dropped around 20%. By controlling the amount and length of the branches in the syndiotactic polypropylene, the permeability of the membrane was enhanced up to 12-fold and it is comparable to typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Regarding the metallocene catalysts, they are characterized by generating poly(propylene) with narrow molecular weight distribution and excellent control of tacticity, they have also proven to be an excellent route for the synthesis of copolymers. For example, alpha‐olefins having different chain length have been incorporated as comonomers in the PP matrix by using metallocene catalysts to obtain copolymers of different compositions and comonomer incorporation, allowing a very good control of the polymerization reaction, high reproducibility and well defined properties of the final product …”
Section: Introductionmentioning
confidence: 99%
“…Regarding the metallocene catalysts, they are characterized by generating poly(propylene) with narrow molecular weight distribution and excellent control of tacticity, they have also proven to be an excellent route for the synthesis of copolymers. For example, alpha‐olefins having different chain length have been incorporated as comonomers in the PP matrix by using metallocene catalysts to obtain copolymers of different compositions and comonomer incorporation, allowing a very good control of the polymerization reaction, high reproducibility and well defined properties of the final product …”
Section: Introductionmentioning
confidence: 99%
“…Vanegas et al [42] also reported that O 2 =N 2 selectivity, in metallocene catalyst syndiotactic polypropylene copolymers, is affected mainly by diffusivity selectivity. With 3% clay addition permselectivity remained constant, with zeolite loading, compared to that of neat PE-LD (Fig.…”
Section: Gas Barrier Propertiesmentioning
confidence: 96%